Evaluating Six Commercially Available Closed-System Drug-Transfer Devices Against NIOSH's 2015 Draft Vapor Protocol. (December 2020) - Halloush, Shiraz; Reveles, Ivan A.; Koeller, Jim
Purpose: In 2015, the National Institute for Occupational Safety and Health (NIOSH) published a draft vapor containment protocol to quantitatively evaluate combined liquid, aerosol, and vapor containment performance of commercially available closed-system drug-transfer devices (CSTDs) that claim to be effective for gas/vapor containment within a controlled test environment. Until the release of this proposed protocol, no standard method for evaluating airtightness of CSTDs existed. The aim of this study was to evaluate six commercially available CSTDs utilizing NIOSH draft protocol methodology to evaluate vapor containment under a robust vapor challenge.Methods: In this study, six commercially available CSTDs were tested utilizing draft NIOSH vapor containment protocol methodology to simulate drug compounding and administration using 70% isopropyl alcohol (IPA) as the challenge agent. All device manipulations were carried out in an enclosed test chamber. A Miran sapphIRe gas analyzer was used to detect IPA vapor levels that escaped the device. Study test included the two tasks designated by the NIOSH protocol, with additional steps added to the evaluation. Tasks were repeated 10 times for each device.Results: Only three of the six tested CSTDs (Equashield®, HALO®, and PhaSealTM) had an average IPA vapor release below the quantifiable performance threshold (1.0 ppm) for all tasks performed. This value was selected by NIOSH to represent the performance threshold for successful containment. The remaining three CSTDs had vapor release above 1 ppm at various times during the IPA manipulation process.Conclusion: Equashield®, HALO®, and PhaSealTM devices tested met the 2015 NIOSH protocol quantifiable performance threshold, functioning as a truly closed system. Quantifiable effective data may be useful in product selection.